Relevance, commitment, and impact : Aspirational formulations of investing-related influencer collaborations in the context of ethical fashion - Hirsto, Heidi; Hjerppe, Cecilia (Nordicom, 2025)
In contemporary society, social media influencers have become mediators of not only commercial but also political and cultural meanings, and their roles are diversifying. In this study, we focus on a nascent phenomenon of “investing-related influencer collaborations”, where influencers act as and address followers as (potential) investors in the context of ethical business. To explore this type of collaboration, we study two empirical cases where lifestyle and fashion influencers run investing-related campaigns with self-proclaimed ethical fashion companies. We analyse these campaigns from a discourse-analytical perspective, identifying three aspirational-affective formulations through which influencers give meaning to investing-related collaborations: renewal of relevance, long-term commitment, and concrete impact. These formulations draw on and rearticulate discourses of investing in relation to evolving influencer roles and ethico-social aspirations. The article shows how the specific forms that influencer collaborations take are connected to wider processes of relational and identity work in the context of promotional politics.
Keywords: influencer collaborations; influencer culture; promotional politics; ideological intermediaries; discourse analysis; investing; fi=Viestintätieteet|en=Communication Studies|